2014
DOI: 10.4049/jimmunol.1400118
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab Efficiently Depletes Increased CD20-Expressing T Cells in Multiple Sclerosis Patients

Abstract: In multiple sclerosis (MS4) B cell depleting therapy using monoclonal anti-CD20 antibodies, including rituximab (RTX) and ocrelizumab (OCR), effectively reduces disease activity. Based on indirect evidence, it is generally believed that elimination of the antigen presenting capabilities and antigen non-specific immune functions of B cells underlie the therapeutic efficacy. However, a small subset of T lymphocytes (T cells) was shown to also express CD20, but controversy prevails surrounding the true existence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
292
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(324 citation statements)
references
References 36 publications
28
292
1
3
Order By: Relevance
“…To address this issue, we have sorted CD3 + CD20 + T cells directly from blood and determined the transcription of CD20. We found that-in contrast to conventional T cells-this T cell subset transcribes CD20, consistent with recent data (11). We also found that these CD3 + CD20…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…To address this issue, we have sorted CD3 + CD20 + T cells directly from blood and determined the transcription of CD20. We found that-in contrast to conventional T cells-this T cell subset transcribes CD20, consistent with recent data (11). We also found that these CD3 + CD20…”
Section: Discussionsupporting
confidence: 81%
“…CD3 + CD20 + T cells produce more readily the cytokines IL-4, IL-17, TNF-a, and IFN-g than CD3 + CD20 2 T cells and respond to immunomodulatory drugs. Our analysis demonstrates a CD3 + CD20 + population comprising 3-5% of all lymphocytes in human blood, corroborating previous reports (11,13). This cell population is a T cell subset because these cells transcribe CD3 at a similar level as conventional T cells and lack surface molecules found on B cells such as CD19, CD40, and HLA-DR. All this justifies to call this population CD20 expressing T cells.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Depletion of a small subset of CD20+ T cells in patients with MS treated with rituximab has also been reported [104]. The effectiveness of rituximab therapy depends on efficient depletion of noncirculating B cells and is associated with qualitative immunological changes that indicate reconfiguration of B-cell memory through sustained reduction of autoreactive clonal expansions and Bcell repopulation characterized by the predominance of IL10-producing Bregs [51,79].…”
Section: Inflammatory Myopathiesmentioning
confidence: 97%